Simulated data for "Small-angle scattering tensor tomography algorithm for robust reconstruction of complex textures" - Leonard Nielsen; Paul Erhart; Manuel Guizar-Sicairos; Marianne Liebi (Chalmers University of Technology, 2023)
These are HDF5 files with the 15 simulated data sets which are used in the work "Small-angle scattering tensor tomography algorithm for robust reconstruction of complex textures", intended for use with the software MUMOTT.

MUMOTT is obtainable via PyPI.
Keywords: small-angle scattering; tensor tomography; reciprocal space map; Physical Sciences; Fysik